2009
DOI: 10.1021/bi802295z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of Copper- and Nickel-Substituted Analogues of Metallo-β-lactamase L1

Abstract: In an effort to further probe metal binding to metallo-β-lactamase L1 (mβl L1), Cu-(Cu-L1) and Nisubstituted (Ni-L1) L1 were prepared and characterized by kinetic and spectroscopic studies. Cu-L1 bound 1.7 equivalents of Cu and small amounts of Zn(II) and Fe. The EPR spectrum of Cu-L1 exhibited two overlapping, axial signals, indicative of type 2 sites with distinct affinities for Cu(II). Both signals indicated multiple nitrogen ligands. Despite the expected proximity of the Cu(II) ions, however, only indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…The exception is Cu(II), which renders MIM-2 significantly more reactive Table 4 indicate that with respect to the β-lactamase activity of MIM-1 and MIM-2, Zn(II) is the preferred metal ion, they also demonstrate that substrate preference is affected by the metal ion composition, and thus alternative in vivo functions may be possible for these enzymes. A similar behavior was observed previously for the B3-type MBL L1 from S. maltophilia, where the substrate specificity for the Ni(II) and Cu(II) derivatives of that enzyme varies distinctly from that of the Zn(II) derivative [53]. Here, a particularly intriguing observation was that Ca(II) was rather proficient in reconstituting ampicillinase activity in MIM-1 (Table 4).…”
Section: The Role Of the Metal Ions In The Reactions Catalyzed By Mimsupporting
confidence: 87%
“…The exception is Cu(II), which renders MIM-2 significantly more reactive Table 4 indicate that with respect to the β-lactamase activity of MIM-1 and MIM-2, Zn(II) is the preferred metal ion, they also demonstrate that substrate preference is affected by the metal ion composition, and thus alternative in vivo functions may be possible for these enzymes. A similar behavior was observed previously for the B3-type MBL L1 from S. maltophilia, where the substrate specificity for the Ni(II) and Cu(II) derivatives of that enzyme varies distinctly from that of the Zn(II) derivative [53]. Here, a particularly intriguing observation was that Ca(II) was rather proficient in reconstituting ampicillinase activity in MIM-1 (Table 4).…”
Section: The Role Of the Metal Ions In The Reactions Catalyzed By Mimsupporting
confidence: 87%
“…68 Crowder et al reported that two cupric ions can be incorporated into the same site, when the apo-form crystals of metallo-β-lactamase is soaked with Cu 2+ , because of metal-binding promiscuity (Figure 9a). 69 Thus, we tried to develop an artificial dinuclear copper oxidase by using metallo-β-lactamase as a platform for dinuclear copper reaction center. 70 We have succeeded in the preparation of copper-substituted metallo-β-lactamase in the periplasm of E. coli cells during the cultivation by using the copper-containing medium.…”
Section: Development Of An Artificial Dinuclear Copper Oxidasementioning
confidence: 99%
“…In the line C region we identified 20 nonsynonomous amino acid changes in conserved validated genes between SS and BN, of which Mblac1, Il3ra, Spry3, Elfn1 , and Azgp1 were predicted by PolyPhen to be damaging variants (Table 1). Mblac1 is a poorly characterized metal-binding enzyme 35 with no reported role in BP or renal function. Il3ra and Spr3 are involved in hematopoiesis 36 and neurogenesis, 37 respectively, but also have no reported role in BP or renal function.…”
Section: Discussionmentioning
confidence: 99%